2005
DOI: 10.1371/journal.pgen.0010078
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Associations of Gene Expression Variation in Humans

Abstract: The exploration of quantitative variation in human populations has become one of the major priorities for medical genetics. The successful identification of variants that contribute to complex traits is highly dependent on reliable assays and genetic maps. We have performed a genome-wide quantitative trait analysis of 630 genes in 60 unrelated Utah residents with ancestry from Northern and Western Europe using the publicly available phase I data of the International HapMap project. The genes are located in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
444
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(461 citation statements)
references
References 38 publications
15
444
1
1
Order By: Relevance
“…We resorted to identify transacting mitochondrial eQTLs (ie, the mtDNA expression-controlling SNPs located in autosomes). However, using the established method, 46 we detected no significant eQTL relationships between autosomal SNPs and mtDNA gene expression. Finally, we examined the existence of indirect links.…”
Section: Effects Of Subcellular Co-localizationmentioning
confidence: 64%
See 1 more Smart Citation
“…We resorted to identify transacting mitochondrial eQTLs (ie, the mtDNA expression-controlling SNPs located in autosomes). However, using the established method, 46 we detected no significant eQTL relationships between autosomal SNPs and mtDNA gene expression. Finally, we examined the existence of indirect links.…”
Section: Effects Of Subcellular Co-localizationmentioning
confidence: 64%
“…Associations between gene expression and genotype (eQTLs) have been established for many nuclear genes. 8,9,[43][44][45][46] We hypothesized that the expression variation of mtDNA genes may be associated with genotypes defined by autosomal SNPs, although the regulatory mechanisms through which these SNPs might affect mtDNA gene expression is not clear. Because all SNPs in mtDNA were of low frequency (MAFo10%), no cis-acting mitochondrial eQTLs (ie, the expression-controlling SNPs located in mtDNA) could be detected.…”
Section: Effects Of Subcellular Co-localizationmentioning
confidence: 99%
“…A great volume of transcriptional expressions that are regarded as quantitative traits can be analyzed using the transcriptional expression QTL (eQTL) mapping aproaches (Brem et al, 2002;Schadt et al, 2003;Morley et al, 2004;Stranger et al, 2005;Wang et al, 2006). Several methods for eQTL mapping also motivate the modeling scheme of multiple quantitative trait mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have suggested that SNPs also have impacts on gene expression variations in human populations (6)(7)(8)(9). Stranger at al.…”
Section: Introductionmentioning
confidence: 99%
“…Stranger at al. (6) found that many regions within 1Mb of 374 expressed genes of interest had significant association of SNPs with expression variation. Stranger et al (7), performing association analyses of expression levels of 14,925 transcripts with SNPs and copy number variants (CNVs) using multiple linear regression, suggested that SNPs captured 83.6% of the total detected genetic variation in gene expression.…”
Section: Introductionmentioning
confidence: 99%